Monitoring the Occurrence of Alarms in IoT-Based HFNC With Analysis of Signal Increase Before Blockages Error Occurs (Pressure Parameters) - Dwi Widyaningtyas; Andjar Pudji; Muhammad Ridha Mak'ruf (Jurnal Teknokes, 2023)
The workload of medical personnel in handling COVID-19 is quite high due to limited personnel so that medical personnel who are resting are assigned the task of always being ready to carry out clinical monitoring of the use of HFNC. HFNC (High flow Nasal Cannula) is a method of giving supplemental oxygen to patients experiencing acute respiratory failure. The use of HFNC in recent years is highly recommended as a solution to provide additional oxygen to patients. The administration of HFNC to COVID-19 patients begins in the flow range of 30-50 LPM with an oxygen concentration of 92%. This study aims to analyze the error in HFNC which causes a decrease in the flow of HFNC. This study used data collection 10 times by modifying the HFNC output interval. The independent variable in this study is the HFNC error condition. While the dependent variable in this study is the pressure data read by the pressure sensor. In this study using a temperature setting of 34oC with a flow setting of 30-60 LPM. At the flow setting of 30 LPM, the average pressure value before error is 0, in process 2 and after error 0, where the IoT notification and the condition of the tool show a Blockage error. At the flow setting of 30 LPM, the average pressure value before error is 0, in process 1 and after error 0, where the IoT notification and the condition of the tool show a leaking error. In this study, the average error in the conditions of Blokage 3.8 and Leaking 1.5 The shortcomings in this study are can be a pressure sensor which has more sensitive results and also a pressure sensor that has a medical grade standard.